THE USE OF KWL METHOD IN TEACHING AND LEARNING PROCESS OF READING COMPREHENSION IN JUNIOR HIGH SCHOOL - Grace Widya Prastika (English Education Department Slamet Riyadi University Surakarta, 2021)
Nowadays, English is the only language that links the whole world and must be learned. In learning English, there were 4 language skills. One of which was reading. Enriching reading would improve student comprehension to communicate through speaking, listening, and writing. The purposes of the study were to describe the problems faced by the teacher and the solutions in teaching and learning process, and also the use of KWL Method in teaching and learning process of reading comprehension. The subject of the research were the teacher and first grade students of SMP N 27 Surakarta in 2020/2021 Academic Year in class A. The data collected by direct observation, and it could be words, interview, and documentation. The data would be described by used qualitative data analysis method. The theoretical basis used teaching and learning reading comprehension. The result showed the teacher chose the KWL because it was good for assessing the development students’ reading skills. However, from KWL method, 60% students were sleepy and did not pay attention, and 40% understood. This problem came because the class management and the different of student capability. The conclusion of this study showed KWL Methods would run well if the teacher could manage class by classify which one had good capability to easily understand and which one did not and had distraction when learning process went. the teacher had to pay more attention about how to increase the curiosity and interest of students for want to learn more about grammar and vocabulary. Keywords: Learning Teaching Method, KWL, English, Reading Comprehension